Association of a Variable Number of Tandem Repeats (VNTR) in Glycoprotein Ibα and HPA-2 Alloantigens - Simsek, S; Bleeker, P M M; van der Schoot, C E; von dem Borne, A E G Kr (Thrombosis and Haemostasis, 1994)
The human platelet alloantigen HPA-2 (Koa/Kob) system is involved in two clinical syndromes, neonatal alloimmune thrombocytopenia and platelet transfusion refractoriness. Wb have previously described that the human platelet alloantigens HPA-2a(Kob) and HPA-2b(Koa), are caused by a Thrl45Met amino acid polymorphism in the N-terminal globular domain of the human platelet glycoprotein (GP) Ibα. In the present study the question was addressed as to whether a genetic association exists between this Thrl45Met polymorphism and the recently described variable number of tandem repeat (VNTR) polymorphism in GP Ibα. Such an association has already been suggested by serological analysis (Ishida et al., 1991). This VNTR polymorphism results from a 13-amino-acid sequence repeat in the macroglycopeptide region of GP Ibα. Therefore, we developed a PCR method to analyze the VNTR region of 106 normal individuals who were also analyzed for the HPA-2 polymorphism. In this method genomic DNA derived from mononuclear cells was purified, the polymorphic region was amplified by PCR and was electrophoresed on agarose gels. Differences in the size of the PCR products made VNTR typing possible. Genotyping for the HPA-2 system was done by allele-specific restriction site analysis of PCR products with the restriction enzyme Sfa NI. The DNA derived from 12 HPA-2 (a-b+) subjects, contained only the B variant (with 3 repeats) of the VNTR polymorphism. The D variant (with 1 repeat) was only found in HPA-2a positive individuals. The C variant (with 2 repeats) was found to be strongly associated with HPA-2a. However, two members of a family with a HPA-2 (a+b+) genotype were found to be homozygous for the C variant of the VNTR polymorphism. This shows that the C variant can also be associated with HPA-2b. The A variant (with 4 repeats) was not encountered in the population studied. The strong association of HPA-2 and VNTR polymorphism, lying 761 bp apart on the GP Ibα gene, indicates linkage disequilibrium.